Ethnic and national varieties of Islam – materials from field research in North-Eastern Bulgaria, 2007–2009 - Kijewska, Anna (Balcanica Posnaniensia. Acta et studia, 2010)
The article presents the results of field research conducted between 2007 and 2009 in northeastern Bulgaria, focusing on the ethnic and cultural diversity of the Muslim communities inhabiting this region. The aim of the study is to demonstrate the local varieties of Islam and to examine the role of religion as one among several factors shaping the ethnic and national identities of these communities. The author analyzes phenomena observed among Turks, Bulgarian Muslims (Pomaks), Turkish Roma, and other groups professing Islam. The empirical material was collected through participant observation and ethnographic interviews in the town of Vǎrbitsa and surrounding villages. The findings reveal that ethnic affiliation in the Gerlovo region is determined by multiple factors such as religion, language, tradition, historical memory, and neighborly relations. The author highlights the interpenetration of cultural elements between Christians, Sunnis, and Shiites, which leads to the emergence of local variants of so-called „folk Islam.” The examples described – including the religious practices and customs of the Turkish Roma – illustrate the dynamic nature of ethnic identity and the influence of globalization, migration, and religious processes on cultural transformations. In conclusion, the study emphasizes the necessity of abandoning the national-state model in favor of a multicultural and pluralistic society based on equal rights and interethnic dialogue. The paper constitutes an important contribution to research on the complexity of religious and national relations in Southeastern Europe.